The randomized embedded multifactorial adaptive platform for community-acquired pneumonia (REMAP-CAP) study: rationale and design - Angus,DC; Berry,S; Lewis,RJ; Al-Beidh,F; Arabi,Y; van,Bentum-Puijk W; Bhimani,Z; Bonten,M; Broglio,K; Brunkhorst,F; Cheng,AC; Chiche,J-D; et al. (Annals of the American Thoracic Society, 2020)
There is broad interest in improved methods to generate robust evidence regarding best practice, especially in settings where patient conditions are heterogenous and require multiple concomitant therapies. Here, we present the rationale and design of a large, international trial that combines features of adaptive platform trials with pragmatic point-of-care trials to determine best treatment strategies for patients admitted to an intensive care unit with severe community-acquired pneumonia (CAP). The trial uses a novel design entitled a randomized embedded multifactorial adaptive platform (REMAP). The design has 5 key features: i.) randomization, allowing robust causal inference; ii.) embedding of study procedures into routine care processes, facilitating enrollment, trial efficiency, and generalizability; iii.) a multifactorial statistical model comparing multiple interventions across multiple patient subgroups; iv.) response-adaptive randomization with preferential assignment to those interventions that appear most favorable, and v.) a platform structured to permit continuous, potentially perpetual enrollment beyond the evaluation of the initial treatments. The trial randomizes patients to multiple interventions within 4 treatment domains: antibiotics, antiviral therapy for influenza, host immunomodulation with extended macrolide therapy, and alternative corticosteroid regimens, representing 240 treatment regimens. The trial generates estimates of superiority, inferiority and equivalence between regimens on the primary outcome of 90-day mortality, stratified by presence or absence of concomitant shock and proven or suspected influenza infection. The trial will also compare ventilatory and oxygenation strategies and has capacity to address additional questions rapidly during pandemic respiratory infections. As of January 2020, REMAP-CAP was approved and enrolling patients in 52 ICUs in 13 countries in 3 continents. In February, it transitioned into pandemic mode wi